2006
DOI: 10.1002/jbm.b.30573
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan scaffolds for in vitro buffalo embryonic stem‐like cell culture: An approach to tissue engineering

Abstract: Three-dimensional (3D) porous chitosan scaffolds are attractive candidates for tissue engineering applications. Chitosan scaffolds of 70, 88, and 95% degree of deacetylation (% DD) with the same molecular weight were developed and their properties with buffalo embryonic stem-like (ES-like) cells were investigated in vitro. Scaffolds were fabricated by freezing and lyophilization. They showed open pore structure with interconnecting pores under scanning electron microscopy (SEM). Higher % DD chitosan scaffolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 38 publications
1
85
1
Order By: Relevance
“…40,41 Many researchers have attempted to measure the swelling ratio of materials using gravimetric method. 42,43 However, the method may give us inaccurate information since loss of solution such as dropping or absorption ability of blot paper during process. Therefore, in order to make up for weak point of gravimetric method, volumetric method which measures the amount of remaining volume of water (PBS in this study) in the system, was used supplementally.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 Many researchers have attempted to measure the swelling ratio of materials using gravimetric method. 42,43 However, the method may give us inaccurate information since loss of solution such as dropping or absorption ability of blot paper during process. Therefore, in order to make up for weak point of gravimetric method, volumetric method which measures the amount of remaining volume of water (PBS in this study) in the system, was used supplementally.…”
Section: Resultsmentioning
confidence: 99%
“…Different kinds of scaffolds, including natural or synthetic polymerbased and polymer blends, have been considered for tissue engineering [5][6][7][8][9][10]. Currently, biomimetic natural biopolymer scaffolds have acquired significance as tissue scaffolds for tissue regeneration because of their superior biological response compared with synthetic scaffolds [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research demonstrated that highly deacetylated chitosan scaffolds are cytocompatible with buffalo embryonic stem cells [7,23]. Interestingly, the pluripotent characteristics of buffalo ES cells could be maintained on chitosan scaffolds when cell-scaffold constructs were studied for 28 days.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in stem cell technology play a key role in the fabrication of functional organs. Embryonic stem cells, adult stem cells, induced pluripotent stem cells, and tissuespecific cell lines can be used for this application [61][62][63][64][65]. However, several challenges remain to be addressed before the actual application of organ printing.…”
Section: Use Of Heart Printing Technology Can Benefit Patients With Hmentioning
confidence: 99%